Landscape-Scale Management of Exotic Forest Plantations: Synergy Between Deadwood and Clear-Cutting Synchrony Modulates Saproxylic Beetle Diversity - Vergara-Egert, P; Fierro-Tapia, C; Alaniz-Baeza, A (Springer, 2020)
Context: Although saproxylic beetles use deadwood in industrial exotic forest plantations, deadwood and historical land use patterns may interact among each other making difficult the implementation sustainable management intended to conserve saproxylic beetle diversity. Objectives: We assessed the additive and interactive effects of deadwood and landscape-scale variables on alpha (α) and gamma (γ) diversity of saproxylic beetles. Methods: We installed 1034 traps in 80 stands of pine/eucalyptus plantations, clear-cuts and native forest distributed in 29 1-km radius landscape units. Deadwood amount/diversity and composition (native vs. exotic) were estimated for each habitat. A 14-year image time series was used to estimate the cover of native forest and the temporal coefficient of variation of clear-cut cover, CV(CC), an indicator of how extensive clear-cut areas have been in each landscape. Results: The amount/diversity of deadwood affected positively the α-diversity of all species, but its effect turned negative in clear cut stands. Exotic deadwood had an overall negative effect on α diversity of fungivores and was more marked as the cover of native forest increased within landscapes. The γ diversity of all species and predators responded negatively to CV(CC), while fungivores responded negatively to the current native forest cover. Deadwood and landscape-scale management had nonlinear effects on γ diversity, with the deadwood composition effect being dependent on clear-cut cover. All species and predators were less diverse as the proportion of exotic deadwood increased, but this effect turned positive within landscapes with high CV(CC). Conclusions: Landscape-scale forest management has long- and short-term effects on saproxylic beetles that are modulated by deadwood and propagate through species functional dimensions. © 2020, Springer Nature B.V.